2021
DOI: 10.1007/s40171-021-00266-w
|View full text |Cite
|
Sign up to set email alerts
|

Environment Practices Mediating the Environmental Compliance and firm Performance: An Institutional Theory Perspective from Emerging Economies

Abstract: Coercive pressure has forced firms to take up environmental measures in the last two decades in emerging economies. Under normative pressure, large firms with farsightedness take up the environmental practices as industry leaders. In a little mature emerging economy, such as India, where triple bottom line awareness is growing, the government facilitates the firms to operate in an environment-friendly ecosystem. We investigate how do environmental compliance and environmental practices influence the overall fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 140 publications
(284 reference statements)
2
24
0
Order By: Relevance
“…A firm's environmental performance mediates the relationship among GSCM practices and financial performance in manufacturing companies (Al-Ghwayeen and Abdallah, 2018). A firm's environmental performance also mediates the relationship among the institutional pressures and a firm's financial performance (Gupta and Gupta, 2021). Future studies should be conducted to investigate the direct influence of institutional pressures on the environment and the indirect effect on firm financial performance (Yang, 2018).…”
Section: Mediating Role Of Environmental Performance Between Green Su...mentioning
confidence: 99%
“…A firm's environmental performance mediates the relationship among GSCM practices and financial performance in manufacturing companies (Al-Ghwayeen and Abdallah, 2018). A firm's environmental performance also mediates the relationship among the institutional pressures and a firm's financial performance (Gupta and Gupta, 2021). Future studies should be conducted to investigate the direct influence of institutional pressures on the environment and the indirect effect on firm financial performance (Yang, 2018).…”
Section: Mediating Role Of Environmental Performance Between Green Su...mentioning
confidence: 99%
“…Hotel managers are playing the role of an agent and they are compelled to comply with the environmental rules imposed by the local council or relevant associations. In many instances, the design and implementation of green policies are due to strong institutional pressure (Gupta & Gupta, 2021). Likewise, Ouyang et al (2019) explained that the institutional environments, such as the regulative environment (e.g., government regulation and policies), normative environment (e.g., competitors' practices and industry association that can detect the norms and standards in the industry), and the expectations from other stakeholders exert considerable pressures on hoteliers to engage in green practices.…”
Section: Subjective Normsmentioning
confidence: 99%
“…Implementation of the social responsibilities of a company largely influences its SC activities, operational performance, supplier performance, and customers’ satisfaction that drive the financial success of a company (Mani et al, 2020 ). Though SS has become an inevitable stepping-stone for a company’s success, it has not gained so much attention like environmental and economic sustainability in the previous literature (D’Adamo et al, 2019 ; D’Eusanio et al, 2019 ; Gupta & Gupta, 2021 ; Kala et al, 2020 ; Somani et al, 2020 ). Most importantly, no study found the critical challenges to SS in the post-COVID-19 context.…”
Section: Literature Reviewmentioning
confidence: 99%